COMPARATIVE EVALUATION OF THE EFFICACY OF LIGNOCAINE AND BENZOCAINE PATCHES FOR VARIOUS DENTAL TREATMENTS IN CHILDREN - Rai, Kavita; Hegde, Amitha M.; Jacob, Mary; Charyulu, R. Narayana (Journal of Health and Allied Sciences NU, 2014)
This study was done to evaluate the clinical efficacy of lidocaine and benzocaine patches in various dental treatment in children. A total of 120 patients were divided into two groups, i.e Group A and Group B. Group A, consisted of 60 children where lignocaine patches were placed and Group B where Benzocaine patches were placed. For each group, the onset of action was recorded after checking for symptoms of anesthesia, subjective and objective pain assessment was evaluated by the VAS and the SEM scale. There was an earlier onset of action which was seen for Lignocaine compared to Benzocaine. But when each of the treatments were compared the anesthetic effect from patches kept the patient comfortable for minimally invasive procedures like band adaptation and was statistically significant. The VAS(Visual analogue scale) scores recorded were statistically significant for the pulpectomy procedure for Benzocaine group compared to Lignocaine. SEM (Sound eyes motor scale) scores were suggestive that the children were more comfortable with the Lignocaine patches when compared to Benzocaine patches.(p <0.0001).The extraction procedures of only grade 3 mobile teeth, pulp therapy for non-vital teeth and band adaptation were clinically successful for both the groups. Our study concluded that, bioadhesive patches can be an alternative over infiltration anesthesia in minimally invasive dental procedures and also could be used successfully for reducing the pain of nerve blocks for children as well as adults which has to be administered in the case of more invasive procedures like pulp therapy.
Keywords: Topical anesthesia; Lidocaine; Benzocaine; patch